The Effects of LAR, LDR, NPL, CAR, and MRR on the Profitability of Banks Listed on the IDX with Bopo as a Control Variable - Haryanto, Temmy; Sitorus, Riris Rotua (Dinasti Publisher, 2025)
This study uses BOPO as a control variable to examine how the profitability of conventional banks listed on the Indonesia Stock Exchange (IDX) is affected by the Loan-to-Asset Ratio (LAR), Loan-to-Deposit Ratio (LDR), Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), and Minimum Reserve Requirement. Using data from bank annual reports for 2018–2024 and a purposive sampling technique, profitability is determined by return on equity (ROE). Multiple linear regression was used in the analysis. The findings of statistical tests show that the independent factors greatly impact profitability simultaneously. In part, LDR has a positive impact, NPL and the Minimum Reserve Requirement have no effect, while LAR and CAR have a negative impact. The Adjusted R2 value sees the independent factors' contribution to profitability of 39.7%.